PENGARUH KESADARAN DESTINASI TERHADAP CITRA DESTINASI DAN NIAT BERKUNJUNG PADA TURIS MILENIAL MELALUI MEDIA SOSIAL INSTAGRAM DI YOGYAKARTA - Niken Permata Sari; Rochmah Insani (Departemen Manajemen, 2020)
Lately, social media has become a means of obtaining information, digital communication and promotional media for tourism destinations. In other words, social media has the potential to participate in efforts to improve the tourism industry. One of social media that is now widely used to find tourism destinations information is Instagram. This study aims to examine the influence destination awareness to destination image and visit intention. Besides that, this study aims to examine the influence destination image to visit intention. This research was conducted based on quantitative approach. Data collected using online survey and envolved 191 respondent. Data analysis was employed using AMOS-SEM. The results of hypothesis testing revealed that destination awareness have a positive impact on destination image and visit intention. Other result showed that image destination have a positive impact on visit intention